In Vitro Analysis of SCUBE1 Expression in Aortic Vascular Smooth Muscle Cells on Atherosclerosis Progression - Rasya, Salsabila Faiha Wiendra; Ali, Hirowati; Yanni, Mefri; Rita , Rauza Sukma; Asri , Aswiyanti; Mahata , Liganda Endo; Putri , Biomechy Oktomalio; Yarni , Sisca Dwi (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2026)
Background: Signal peptide-CUB-EGF domain-containing protein-1 (SCUBE1) is a platelet–endothelial glycoprotein implicated in thrombosis and vascular inflammation, and has been detected within atherosclerotic lesions. Whether vascular smooth muscle cells (VSMCs) upregulate SCUBE1 under inflammatory stimuli remains unclear. Objective: To quantify SCUBE1 mRNA expression in rat aortic VSMCs following lipopolysaccharide (LPS) exposure in an organ-culture model of atherogenesis. Methods: This study aimed to analyze SCUBE1 expression in aortic VSMCs in atherosclerosis using real-time PCR. This study was a true experimental-post test control group design using organ culture. The aorta from six wistar rats were divided into two groups, consisting of five samples that were not induced with LPS and five samples exposed to LPS at a concentration of 10 µg/mL for 48 hours. Expression of the SCUBE1 gene was then analyzed using real-time PCR. The data was then processed using the dependent T-Test. Results: The result showed LPS increased SCUBE1 transcript levels compared with control (mean ± SD: 0.78 ± 0.22 vs 0.44 ± 0.35), representing a non-significant trend toward induction (p=0.07). These preliminary data are consistent with SCUBE1’s inducibility in inflammatory states and its presence in atherosclerotic tissue. Conclusion: This study revealed increased SCUBE1 gene expression in aortic VSMCs in the LPS-treated group. These data suggest that SCUBE1 has the potential to be a marker of endothelial dysfunction in atherosclerosis.